ISBAT RAMADHAN in THE PERSPECTIVE of AL-QUR'AN - Ade Jamrudin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The Qur'an revealed by Allah is not only to be read textually, but the Qur'an to be understood, lived and practiced in social life of society. The Qur'an revealed to the Muhammad is to elevate the human level from the valley of darkness to a brightly lit world. History proves that jahiliyyah society which has no civilization and direction and purpose of life successfully brought by the Muhammad to the new life of a more advanced civilization, the life of the illuminated light of faith and respect for the dignity of humanity. Differences determining the beginning of fasting and syawwal, it turns out that the difference is just on the determination of criteria. According to the experts the cause of the difference is not the difference between the method of calculation and observation, but more because of differences in understanding the provisions written in the holy book of the Qur'an and the hadith of Muhammad